The reference in the verses of sleep in the Quran and its effect on the text coherence - Hasan Jawad, Hamasat Mohammed (Opción, 2019)
Referral is one of the most important means of textual coherence. It plays a vital and important role in the cohesion of texts. It is indispensable for any text, because it is the basis and structure on which these texts are based. The reference in the nine verses of sleep in the Holy Quran, all kinds of referral pronouns, and referral by the name of the signal, as well as the name connected. The assignment was linked to all its sections between short and long senten- ces, creating a communication relationship between the text and the recipient. The linguistic miracle of the Holy Qur'an, and the ability of the Lord of Glory in the formation and management of the universe, were revea- led by reducing many of the events in the verses of sleep, with almost no pronouns and names of references and references referred to many to avoid repetition.